Agronomic interventions for enhancing diverse agroecosystems services - Avasthe, Ravikant; Kumar, Amit; Saha, Saurav; Singh, Raghavendra; Babu, Subhash (Indian Farming, 2021)
Agroecosystem services signify the common interface between agroecological functioning and seasonal production economics of any particular agro-ecosystem that divulges viable nature-human interactions maintaining environmental quality. Agriculture and ecosystem services are interconnected in different ways. Agronomic interventions in agricultural ecosystems provide food, forage, bioenergy, etc. which are essential for human and animals. These interventions produce a variety of ecosystem services, such as regulation of soil and water conservation, carbon sequestration, support for biodiversity, increase the pollination, natural plant protection, increased productivity, provide healthy food, improved soil quality, improved environmental quality, nutrient cycling and hydrological services. Payments for ecological services (PES) provide opportunities for augmenting ecosystem services in agroecosystems. Beneficial actions will depend on strong supporting policies and legal frameworks, besides developing the knowledge and leadership capacity in farming communities to evaluate the prospective payback.